Analysis of vertical total electron content (VTEC) from different IGS products and VTEC anomalies for the detection of earthquake precursor - Prapas Thammaboribal; Tripathi, Nitin Kumar; Pal, Indrajit; Sarawut Ninssawat; Royal Thai Government; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2022)
The main objective of this study is the development of seismo-ionospheric anomaly detection technique by applying the average of diurnal vertical total electron content (AVTEC) as well as the standard deviation of diurnal vertical total electron content (SVTEC) instead of the conventional techniques as applying background window for detecting the VTEC anomaly. In this study, 38 earthquakes vary from light earthquakes (M4<M<M5) to great earthquakes (M>8) were selected as case studies. The epicenters of the earthquakes were located in low latitude and middle latitude regions.To investigate the influence of geography on the VTEC anomaly appearance, the earthquakes were also characterized into inland and submarine earthquakes. The results reveal that the ionospheric anomaly cannot be detected at all when the earthquake moment magnitude is lower than 5 (light earthquakes), but the moderate earthquakes and strong earthquakes, the anomalies were significantly detected in low latitude region. In case of a magnitude greater than 7, the anomalies were detected one up to six days prior to the earthquake occurrence. The anomalies detected from inland earthquake cases give the same characteristic of AVTEC and SVTEC distribution which the values of AVTEC and SVTEC decrease proportional to the distance rom the anomalous zone, the anomalous zone usually occurs within the earthquake preparation zone.The ionospheric anomalies of major and great earthquake cases also reveal that the anomaly can be detected both in low latitude and middle latitude but the appearance of the anomaly is more significant in the low latitude region because the ionosphere in the mid latitude in this study is influenced by the crest of onospheric variation n the eguatorial ionization anomaly (EIA). Finally, the anomalous days detected from AVTEC and SVTEC were consistent with previous studies, thus, this novel anomaly detection technique is a promising approach for the further work of the ionospheric disturbance prior 19 earthquake occurrence study.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Engineering in Remote Sensing and Geographic Information Systems
Thesis (Ph.D.) - Asian Institute of Technology, 2022
Keywords: Ionospheric electron density -- Detection -- Technique; Earthquake prediction